Students Voices: A Qualitative Study On Teachers’ Written Feedback Among Fourth Year University Students - Bahri, Syamsul (Association of Language Teachers in Southeast Asia (ALTSA), 2019)
The objectives of this study is to find studentÃ¢â‚¬â„¢s voices on teachersÃ¢â‚¬â„¢ written feedback. The qualitative study investigates the studentÃ¢â‚¬â„¢s voices on teachersÃ¢â‚¬â„¢ written feedback of their essays and comments that benefit studentsÃ¢â‚¬â„¢ future improvement as writers. It explores sixty-one English Department studentsÃ¢â‚¬â„¢ opinions on the written feedback of their writing teachers at Ar-Raniry State University of Islamic Studies, Banda Aceh, Indonesia.Ã‚Â The findings indicate that writing teachers provide various kinds of feedback on studentsÃ¢â‚¬â„¢ essays and they valued positive teachersÃ¢â‚¬â„¢ feedback on all aspects of writing such as grammar, mechanics, content and organisation. TeachersÃ¢â‚¬â„¢ negative comments were also considered useful for studentsÃ¢â‚¬â„¢ learning because they can help students to improve their critical thinking and writing skills. In addition, for student future improvement, teachersÃ¢â‚¬â„¢ feedbacks do contribute to learning and that teachersÃ¢â‚¬â„¢ feedback on grammar and organisation are more preferable than those on content and mechanics. It is suggested that feedback which highlights strengths and weaknesses of studentsÃ¢â‚¬â„¢ work can facilitate students to learn and make better future learning.